Spatial transcriptomics unravels the interactive network of aflatoxin B1-driven gastric cancer: Multi-omics integration of transcriptome and mendelian randomization - Yong-Le Li; Cong Liu; Meng Tang; Wan-Shou Wei; Xiao-Mei Xie; Yuan Gan; Xuan-Hua Chen; Shan-Shan Dong; Li-He Jiang (Ecotoxicology and Environmental Safety)
The escalating threat of widespread exposure to environmental pollutants on human health has drawn increasing attention, particularly regarding mycotoxin contaminants with potent carcinogenic properties. As a prototypical environmental toxin, the molecular mechanisms underlying aflatoxin B1-induced gastric carcinogenesis remain poorly defined. This study systematically elucidates the molecular network through which aflatoxin B1 (AFB1) synergistically drives the malignant progression of gastric cancer by specifically targeting five core regulatory genes, exemplified by its upregulation of cyclin genes CCNE1 and CCNE2. Molecular docking simulations demonstrate significant binding activity between AFB1 and the core targets, with MAPK3 exhibiting the optimal binding affinity as evidenced by the most favorable binding free energy. Integrated single-cell RNA sequencing of human gastric cancer tissues and spatial transcriptomics (10X Visium) revealed cell-type-specific expression patterns of these core target genes within immune cell clusters in the tumor microenvironment, particularly in T cell subpopulations. Innovatively, this study constructs a multi-layered molecular regulatory map of AFB1-induced gastric carcinogenesis, establishing a novel paradigm for multi-omics integration in elucidating the toxicological mechanisms of environmental carcinogens.